Coronary Atherosclerotic Calcification - Sony Hilal Wicaksono; Christian Setiawan; Indah Fitriani (MEDICINUS, 2024)
Coronary artery disease is a significant public health concern in Southeast Asia, including Indonesia. It is characterized by the buildup of atherosclerotic plaques within the coronary arteries, leading to reduced or interrupted blood flow to myocardium. A hallmark of atherosclerosis is calcification, which may occur during both plaque progression and regression. To date, it remains unclear whether the progression of atherosclerotic lesions follows a linear pattern. The formation of microcalcifications initiates the calcification process and warrants further investigation. Several imaging modalities, which have significantly advanced, may help measure the coronary artery calcification burden and guide appropriate management. Concerns about radiation exposure have positioned coronary artery calcium scoring as the most effective,efficient, and readily observable parameter among both invasive and non-invasive imaging techniques. Identifying highrisk plaque characteristics and severe or extensive calcification is essential in order to provide optimal treatment. However, the progression of calcification remains uncertain, and ongoing research is being conducted to explore potential methods to reverse it. Various tools and complex techniques have been developed to address different types of calcified lesions. Further studies are needed to identify patients who experience more rapid calcification progression, in order to optimize preventive strategies.